Immunomodulatory Effect of Flavonoids of Blueberry (Vaccinium corymbosum L.) Leaves via the NF-κB Signal Pathway in LPS-Stimulated RAW 264.7 Cells - Dazhi Shi; Mengyi Xu; Mengyue Ren; Enshan Pan; Chaohua Luo; Wei Zhang; Qingfa Tang (Journal of Immunology Research)
Objective. This study aimed to explore the immunoregulatory effect of flavonoids of blueberry (Vaccinium corymbosum L.) leaves (FBL). Methods. The flavonoids of blueberry leaves were prepared with 70% ethanol and were identified by ultraperformance liquid chromatography/quadrupole-time-of-flight mass spectrometry (UPLC/Q-Tof-MS). The immunoregulatory effect and possible regulatory mechanisms of FBL were investigated in lipopolysaccharide- (LPS-) induced RAW 264.7 cells. Results. According to the results of UPLC/Q-Tof-MS, nine flavonoids of blueberry leaves were identified. FBL showed a significant reduction in the production of TNF-α in LPS-stimulated RAW 264.7 cells. FBL significantly decreased the expression of NF-κB p65 and P-NF-κB p65 in LPS-induced RAW 264.7 cells in a dose-dependent manner. Conclusion. Our study showed the immunoregulatory effect of FBL through the suppression of TNF-α via the NF-κB signal pathway.